Analysis of the Influence of Information Quality, Quantity, and Credibility, as Well as Information Needs and Attitude Towards Information on Information Usefulness and Information Adoption in Enhancing Online Purchase Intention Among Generation Z Through EWOM - Mirelle Valentine Limowa; Sabrina O. Sihombing (Universitas Pelita Harapan, 2024)
Consumer purchase intention is a response that develops in a consumer after receiving stimulation from the product they see, in order to easily influence consumers, PIKARU products innovate through social media with interactive and dynamic content to make the spread of information, opinions, and recommendations faster. The purpose of this study is to ascertain how sociaI media's eIectronic word-of-mouth (e-wom) infIuences Generation Z's desire to buy Pikaru products online. The research sample for this quantitative study, which has 350 respondents overall, includes Gen Z residents in JABODETABEK who are between the ages of 18 and 24 and use Pikaru hair care. A questionnaire that used a Likert scale for measuring was used to collect data. The testing approach used in this study is StructuraI Equation ModeIing-PartiaI Least Square (SEM-PLS) analysis. The resuIts show that online purchasing intentions are highly infIuenced by the following variables: information quality, quantity, credibility, needs, attitude towards information usefulness, and adoption.